The Role Of Green Promotion In Enhancing Consumer Mental Image "A Survey Study On Food Products Consumers In The Syrian Coast" - حبيب, اباء; حنان تركمان; فداء الشيخ حسن (Latakia University Journal - Economic and Legal Sciences Series, 2022)
In the last few years, Syria has remarkable growth regarding to green economy and its implications. Many companies and organizations have adopted several initiatives and attempts to apply green economy in Syria. This research main purpose is to study food companies green promotion and discover the ROLE of it on consumer’s mental image. The researcher has followed the descriptive approach - survey which is based on a survey to study the phenomenon as it exists in reality and the research sample included 150 consumers. Research primary information were collected through a questionnaire, data were analyzed and subjected to needed statistical tests by the SPSS statistical program. After the study and analyze, the research concluded the following: - The consumers' evaluation was average, whereas there were many points that must pay attention to make the turnout bigger. - There is a clear Correlation between the green promotion on one hand and the mental image on the other hand. - Research found that there is a lack of interest in a lot of the elements of the promotion policies, that could affect badly the green promotion.